Advances in the Analysis of Spanish Exclamatives - Bosque, Ignacio (Book collections on Project MUSE., 2017)
'Advances in the Analysis of Spanish Exclamatives' is the first book entirely devoted to Spanish exclamatives, a special sentence type often overlooked by contemporary linguists and neglected in standard grammatical descriptions. The seven essays in this volume, each by a leading specialist on the topic, scrutinize the syntax, as well as the semantic and pragmatic aspects, of exclamations on theoretical grounds. The book begins by summarizing, commenting on, and evaluating previous descriptive and theoretical contributions on Spanish exclamatives. This introductory overview also contains a detailed classification of Spanish exclamative grammatical types, along with an analysis of their main properties.